2005
DOI: 10.1007/s00216-005-0224-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of traditional cloud-point extraction and on-line flow-injection cloud-point extraction with a chemiluminescence method using benzo[a]pyrene as a marker

Abstract: In this work, using benzo(a)pyrene (BaP) as marker, the analytical merits of on-line flow-injection cloud-point extraction (FI CPE), including preconcentration factor, extraction efficiency, sample throughput, and analysis time were evaluated by use of peroxyoxalate chemiluminescence (CL) detection. Moreover, by detailed discussion of several preconcentration conditions for traditional and on-line FI CPE the advantages of on-line FI CPE became conspicuously apparent. When coupled with separation techniques suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 19 publications
1
7
0
1
Order By: Relevance
“…However, organic solvents are toxic, expensive and difficult to be degraded. Recently, studies have demonstrated the use of micellar media as an alternative to organic solvent for extracting organic pollutants from solid environmental samples [21][22][23][24]. Moreover, Huie [25,26] and Ong [27,28] proved that the surfactant solutions in ASE can effectively extract the active ingredients in medicinal plants, and avoid the degradation of thermally unstable ingredients at high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…However, organic solvents are toxic, expensive and difficult to be degraded. Recently, studies have demonstrated the use of micellar media as an alternative to organic solvent for extracting organic pollutants from solid environmental samples [21][22][23][24]. Moreover, Huie [25,26] and Ong [27,28] proved that the surfactant solutions in ASE can effectively extract the active ingredients in medicinal plants, and avoid the degradation of thermally unstable ingredients at high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, compared to the results obtained by other authors [6][7][8][9][10][11][12][13], the present on-line CPE/FIA system had many advantages, such as high sensitivity, high sample throughput, high extraction efficiency and simplicity. Experimental factors which govern the magnitude of the preconcentration factors and the CL intensity were studied.…”
Section: Introductionmentioning
confidence: 83%
“…When compared to all the reported on-line CPE/FIA papers [6][7][8][9][10][11][12][13], the key difference/improvement of the present on-line CPE/FIA system was that the collection column served a dual function: (1) to entrap the analyte-containing surfactant aggregates and (2) to provide CL emission (i.e., the collection column was mounted directly adjacent to the detector). Table 1 shows the effects on the CL intensity as a function of the presence (or absence) of the analyte (bilirubin), surfactant (Triton X-114), salting-out agent (Na 2 SO 4 ) and/or filtering material (cotton).…”
Section: Collection Columnmentioning
confidence: 99%
See 2 more Smart Citations